2011
DOI: 10.1021/bc100584d
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared pH-Activatable Fluorescent Probes for Imaging Primary and Metastatic Breast Tumors

Abstract: Highly tumor selective near-infrared (NIR) pH-activatable probe was developed by conjugating pH-sensitive cyanine dye to a cyclic Arginine-Glycine-Aspartic acid (cRGD) peptide targeting α v β 3 integrin (ABIR), a protein that is highly overexpressed in endothelial cells during tumor angiogenesis. The NIR pH-sensitive dye used to construct the probe exhibit high spectral sensitivity with pH changes. It has negligible fluorescence above pH 6 but becomes highly fluorescent below pH 5, with a pKa of 4.7. This prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
148
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 34 publications
1
148
0
Order By: Relevance
“…Prior elegant works have demonstrated selective tumor imaging using activatable contrast agents, primarily of macroscopic tumors (17,28,29,(42)(43)(44). However, these probes have not been used to treat micrometastases, largely due to the fact that fluorescence-guided surgery is impractical at the microscopic scale.…”
Section: Resultsmentioning
confidence: 99%
“…Prior elegant works have demonstrated selective tumor imaging using activatable contrast agents, primarily of macroscopic tumors (17,28,29,(42)(43)(44). However, these probes have not been used to treat micrometastases, largely due to the fact that fluorescence-guided surgery is impractical at the microscopic scale.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our observations, it has been reported that activatable fluorescent probes exploiting aggregation-induced fluorescence quenching, like ICG-Herceptin 10 or Cy5.5-Herceptin 12 conjugates, produce high liver signals resulting in decreased tumor contrast. Moreover, this probe design strategy that requires the conjugation of several fluorophores to one targeting ligand 12,42 cannot be used for small ligands like peptides that contain often only a single dye binding site, whereas pH-sensitive dyes 7 such as CypHer5E do not have this limitation. Moreover, the conjugation of many fluorophores to a biomolecule results in higher material costs and can reduce bioconjugate stability and binding efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These problems can be circumvented by the use of functional tumor-specific fluorescent probes, which have increasingly been at the focus of various studies in recent years. [7][8][9][10][11][12] However, the majority of these probes are still limited in their sensitivity and specificity, regarding penetration depth and real-time imaging of biological processes in vivo. Therefore, there is an ever-growing demand for the development of probes with, for instance, improved tissue penetration and site-or analyte-specific signaling that display a specific fluorescence signal only when located at the tumor site and remain otherwise dark.…”
Section: Introductionmentioning
confidence: 99%
“…Signals from circulating probe can undesirably degrade contrast between the target and its surroundings. A powerful strategy for minimizing this source of background is to use activatable probes that produce signals only in response to specific cues such as low pH (8,9), endogenous enzyme activity (10,11), or interaction with reporter gene products. Luciferins, for example, generate light only after luciferase-mediated oxidation, providing exceptional contrast between reporter activity and circulating probe (12).…”
Section: Introductionmentioning
confidence: 99%